PENINGKATANÂ HASILÂ BELAJARÂ SISTEMÂ PENGAPIANÂ FULLÂ TRANSISTOR MENGGUNAKANÂ MEDIAÂ PERAGAÂ DISTRIBUTORÂ BOARDÂ PANELÂ Â Â (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Negeri Semarang, 2010)
Penelitian Â ini Â bertujuan Â untuk Â membuat Â media Â peraga Â distributor Â board Â panel Â dan Â mengetahuiÂ peningkatan hasil belajar mahasiswa tentang sistem pengapian Â full transistor setelah menggunakan media peragaÂ tersebut. Penelitian ini menggunakan desain eksperimen semu/Quasi Experiment Design dengan pola pre testÂpostÂ test Â one Â group Â design. Populasi penelitian Â ini Â adalah 100 Â orang mahasiswa program diploma Â (D3) Teknik MesinÂ Universitas Â Negeri Â Semarang Â yang Â mengikuti Â matakuliah Â kelistrikan Â otomoti Â ftahun Â ajaran Â 2009/2010 Â yangÂ terbagi dalam 3 Â rombongan belajar Â (rombel). Satu Â rombel Â (rombel 02) dengan 36 orang dijadikan Â sampel. HasilÂ penelitian menunjukkan Â adanya peningkatan hasil belajar Â sistem Â pengapian Â full Â transistor Â setelah menggunakanÂ media peraga. Nilai rataâ€rata pre test sebelum menggunakan media peraga sebesar 44,46 dan setelah menggunakanÂ media peraga (post test) sebesar 72,42. Nilai mahasiswa mengalami peningkatan 55,94 %.Kata kunci: peningkatan hasil belajar, media peraga distributor board panel, sistem pengapian full transistorÂ The Â objectives Â of Â the Â research Â are Â to make distributor board panel medium Â and Â to Â identify Â the Â resultÂ learning Â improvement about Â full Â transistor ignition system after the use of the mentioned medium. This researchÂ uses quasi experiment design with pre testÂpost test one group design pattern. The population of this research wasÂ about 100 students of diploma program (D3) of Mechanical Engineering Department of Semarang State UniversityÂ (UNNES) Â that Â joined automotive electricity subject year 2009/2010 that was categorized Â into 3 Â learning groups Â .Â One learning group (group 2) with 36 students was taken to be sample. The result of the research shows theÂ learning result Â improvement of Â full Â transistor ignition system after the use of visual display or medium. The rateÂ score of pre test before the use of the medium is about 44,46 and after the use of it (post test) the rate is aboutÂ 72,42. The scores of students get improvement about 55,94%.Keywords: the learning result improvement, distributor board panel medium, full transistor ignition system